Rotational Stability of a New Posterior Chamber Toric Phakic Intraocular Lens - Dilek Yaşa; Bülent Köse; Alper Ağca (Journal of Ophthalmology)
Purpose. To evaluate the refractive results and rotational stability of Eyecryl toric phakic intraocular lens (pIOL). Methods. In this retrospective single-surgeon case series, manifest refraction, visual acuities, endothelial cell density (ECD), and pIOL rotation were evaluated over 6 months. Results. 43 eyes from 23 patients were included. At 6 months, the SE was within ±0.50  D of emmetropia in 30 (70%) eyes and within ±1.00  D of emmetropia in 39 (91%) eyes. The efficacy and safety indices were 1.25 ± 0.38 and 1.41 ± 0.34, respectively. Mean ECD was 2719 ± 296 cells/mm2 at the preoperative visit and 2779.42 ± 422 cells/mm2 at the 6-month visit (p>0.05). The mean value of absolute axis orientation error was 4.95 ± 5.28°. Mean absolute change in axis orientation between visits was less than 3° for all visit intervals. Ninety percent or more of lenses were found to rotate 5° or less between all visit intervals. None of the patients experienced a vision-threatening complication, and no patient required secondary IOL repositioning. Conclusion. The pIOL appears to effectively reduce subjective manifest astigmatism and provide good visual acuity. Its position was found to be stable throughout the follow-up.